Porous Silicon–Based Microring Resonator for Temperature and Cancer Cell Detection - Gangwar, Rahul Kumar; Qin, Jun; Wang, Xingjun (Frontiers in Physics, 2022)
In this article, a microring resonator sensor based on porous silicon is proposed for temperature and cancer cell detection, simultaneously. The porous behavior of silicon with a large internal surface area allows external materials to interact directly with the guided modes. The resonance wavelength in the transmission spectrum of the microring resonator is very sensitive to external environmental properties such as refractive index and temperature. The transmission characteristics of the proposed sensor were numerically determined by full vectorial finite element analysis. The achieved maximum sensitivity of the proposed sensor with optimized parameters was 150 pm/°C for an operational temperature range of 20–100°C and 284.0306 nm/RIU for operational cancer cell detection, respectively. The results presented here suggest the microring resonator sensor can be used in the fields of environment sensing, temperature sensing, chemical sensing, and biosensing.